Determining the Maternal and Fetal Cellular Immunologic Contributions in Preterm Deliveries With Clinical or Subclinical Chorioamnionitis - M. F. McNamara; T. Wallis; F. Qureshi; S. M. Jacques; B. Gonik (Hindawi Limited, 1997)
Objective: Our purpose was to determine the maternal and fetal polymorphonuclear contributions to preterm histologic chorioamnionitis and whether this response differs in clinical chorioamnionitis when compared to cases without clinical chorioamnionitis.